When diaspora identities are in between: The Ahwazis of Northern Europe - Soltani,Nick (2025)
The Iranian diaspora is rather well studied. Researchers have investigated wide topics within the diaspora, from its political activities, the identity of 2nd generation diaspora Iranians, to host society dynamics and nostalgia. These studies reveal an ethno-nationalist attitude, as many in the Iranian diaspora do not adhere to the Persian-dominated identity articulated by the Iranian diaspora. To fill this void, this thesis engages with the Ahwazis in Northern Europe. They are, like other non-Persian speaking ethnic groups of Iran, understudied in research on the Iranian diaspora. While the Ahwazis come from a certain region within Iran and hold Iranian citizenship, they are, unlike the majority of Iranians, ethnically Arab. Smaller groups, such as the Ahwazis, also play a role in transnational politics and international dynamics. This has been exemplified in the late 2010s and 2020’s where, among other things, Ahwazis in Europe were assassinated and jailed, as well as causing tensions between the Iranian state and Denmark, the Netherlands, and Sweden. Although the Ahwazis are a numerically small group, they are active in different political groups and organisations. This thesis engages in what lies behind these political activities: the group identities of the Ahwazis – and it addresses how their complex group identity is built, created, articulated, and challenged by many factors in the contexts in which they find themselves. Likewise, the thesis illuminates how they navigate in a landscape where they are surrounded - and often overshadowed - by larger diaspora communities, such as Persian-speaking Iranians and other Arabs, as their ethno-linguistic identity markers and territorial boundaries and citizenship blur the communal boundaries between them. As the first ever study of Ahwazis outside of Iran, this thesis, through interviews and digital ethnography, detangles these layers of identity and inter-diasporan dynamics. While most diasporas practice boundary-making to distinguish themselves from other diaspora groups and the native population of the country of residence, the Ahwazi case is rather unique. As they are ethnically Arab but Iranian citizens, a special in-between hybridity exists that creates ambiguity in their identities and relations to the Iranian and Arab diasporas. Unlike other transnational diaspora communities with origins in Iran, such as the Kurds, Ahwazis do not have a counterpart that shares their struggle and identities on the other side of the border, which leaves them in a special position in terms of identities, sense of belonging, and alignments.
Keywords: Ahwaz; Iran; Diaspora; Arab; boundary making; nationalism; minorities